The Impact of Economic Factors as Causes of Domestic Violence in the Family (A Study of Besilam Village, Langkat Regency) - Sendy, Beby; Rossanty, Yossie; Hawawari, Muhammad Fadhiil (PT FORMOSA CENDEKIA GLOBAL, 2024)
Domestic Violence (DV) is a pervasive phenomenon that causes significant harm to all parties involved, encompassing social, psychological, and economic dimensions within the familial context. This study seeks to examine and elucidate the economic factors that contribute to the incidence of domestic violence in Besilam Village, Langkat Regency. Employing a qualitative research design through field study methods, data were collected via in-depth interviews with individuals who had either experienced or witnessed domestic violence, supplemented by participatory observations within the local community. The findings underscore the critical role of economic factors in precipitating domestic violence in the study area. To mitigate domestic violence in this village, a multidimensional approach integrating economic, social, and educational strategies is imperative. Moreover, the involvement of governmental and institutional stakeholders is essential in providing protective measures and support services for victims. Social campaigns aimed at enhancing public awareness of the adverse impacts of domestic violence are equally crucial. Domestic Violence (DV) also encapsulates gender-based violence within the private sphere. This form of violence frequently occurs in close personal relationships where the perpetrator is a familiar and trusted individual, such as a husband against his wife, a father against his child, an uncle against a niece or nephew, or a grandfather against a grandchild. Additionally, domestic violence is often characterized as violence against women perpetrated by family members bound by consanguinity.